Leukoencephalopathy‐causing CLCN2 mutations are associated with impaired Cl− channel function and trafficking. (9th October 2017) - Gaitán‐Peñas, Héctor; Apaja, Pirjo M; Arnedo, Tanit; Castellanos, Aida; Elorza‐Vidal, Xabier; Soto, David; Gasull, Xavier; Lukacs, Gergely L; Estévez, Raúl
Abstract : Key points: Characterisation of most mutations found in CLCN2 in patients with CC2L leukodystrophy show that they cause a reduction in function of the chloride channel ClC‐2. GlialCAM, a regulatory subunit of ClC‐2 in glial cells and involved in the leukodystrophy megalencephalic leukoencephalopathy with subcortical cysts (MLC), increases the activity of a ClC‐2 mutant by affecting ClC‐2 gating and by stabilising the mutant at the plasma membrane. The stabilisation of ClC‐2 at the plasma membrane by GlialCAM depends on its localisation at cell–cell junctions. The membrane protein MLC1, which is defective in MLC, also contributes to the stabilisation of ClC‐2 at the plasma membrane, providing further support for the view that GlialCAM, MLC1 and ClC‐2 form a protein complex in glial cells. Abstract: Mutations in CLCN2 have been recently identified in patients suffering from a type of leukoencephalopathy involving intramyelinic oedema. Here, we characterised most of these mutations that reduce the function of the chloride channel ClC‐2 and impair its plasma membrane (PM) expression. Detailed biochemical and electrophysiological analyses of the Ala500Val mutation revealed that defective gating and increased cellular and PM turnover contributed to defective A500V‐ClC‐2 functional expression. Co‐expression of the adhesion molecule GlialCAM, which forms a tertiary complex with ClC‐2 and megalencephalic leukoencephalopathy with subcortical cysts 1 (MLC1), rescued the functional expression of the mutant by modifying its gating properties. GlialCAM also restored the PM levels of the channel by impeding its turnover at the PM. This rescue required ClC‐2 localisation to cell–cell junctions, since a GlialCAM mutant with compromised junctional localisation failed to rescue the impaired stability of mutant ClC‐2 at the PM. Wild‐type, but not mutant, ClC‐2 was also stabilised by MLC1 overexpression. We suggest that leukodystrophy‐causing CLCN2 mutations reduce the functional expression of ClC‐2, which is partly counteracted by GlialCAM/MLC1‐mediated increase in the gating and stability of the channel. Key points: Characterisation of most mutations found in CLCN2 in patients with CC2L leukodystrophy show that they cause a reduction in function of the chloride channel ClC‐2. GlialCAM, a regulatory subunit of ClC‐2 in glial cells and involved in the leukodystrophy megalencephalic leukoencephalopathy with subcortical cysts (MLC), increases the activity of a ClC‐2 mutant by affecting ClC‐2 gating and by stabilising the mutant at the plasma membrane. The stabilisation of ClC‐2 at the plasma membrane by GlialCAM depends on its localisation at cell–cell junctions. The membrane protein MLC1, which is defective in MLC, also contributes to the stabilisation of ClC‐2 at the plasma membrane, providing further support for the view that GlialCAM, MLC1 and ClC‐2 form a protein complex in glial cells.